Adopsi Teknologi dan Pengaruhanya terhadap Produktivitas Padi: Studi Kasus pada Dua Pola Pengairan di Kabupaten Sintang - Rafli Ahmad; Jajat Sudrajat; Anita Suharyani (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study aimed to analyze the level of technology adoption and its effect on rice farming productivity under two irrigation patterns in Sintang Regency. The research was conducted in selected rice farming areas that applied different irrigation patterns. The study employed a quantitative approach using survey methods. Data were collected through interviews with rice farmers using structured questionnaires. The respondents were selected using proportional sampling techniques based on irrigation patterns. The variables observed included the level of technology adoption in land preparation, seed selection, fertilization, pest and disease control, irrigation management, and harvesting activities. Data analysis was conducted using descriptive analysis to measure the level of technology adoption and inferential statistical analysis to examine the effect of technology adoption on rice productivity.The results showed that the level of technology adoption among farmers varied between irrigation patterns, with farmers under more organized irrigation systems demonstrating higher levels of technology application. Technology adoption significantly influenced rice productivity, indicating that improved application of modern agricultural technologies contributed to increased rice yields. These findings highlight the importance of strengthening extension services, improving farmers’ access to agricultural technology, and enhancing irrigation management systems to increase rice productivity in Sintang Regency.